EVIDENCE BASED CASE REPORT (EBCR) : PENGARUH PEMBERIAN PIJAT OKETANI TERHADAP PRODUKSI ASI - Khoirul Barriyah, Jasmine; Sofiyanti, Santi; Resmana, Rika (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Breastfeeding is a nutritional need for babies during growth and development. Breast milk (ASI) helps in sensory, cognitive, and motor development and protects and prevents babies from various diseases and infections. Breast milk production is influenced by the hormones prolactin and oxytocin, food intake, the mother's psychological condition, breast care, and the frequency of breastfeeding. In stimulating the release of these hormones, one of the efforts made is breast care. Breast care will stimulate the breasts and affect the hypopise to release more progesterone, estrogen, and oxytocin hormones. The hormone oxytocin will contract other cells around the alveoli, causing milk to flow down towards the nipple. One of the breast care techniques is oketani massage. This massage is a massage technique popularized in Japan that will make the breasts softer, the areola and nipples elastic, making it easier for babies to suckle breast milk. Objective: To determine the effect of oketani massage on postpartum maternal breast milk production. Method: This journal search uses keywords, Boolean Operators and E-data based with literature review and experimental research types. Results: Based on this study, it was found that there was an effect of Oketani massage on breast milk production in postpartum mothers. Conclusion: It is expected that health workers can use the Oketani massage technique to help breast milk production in postpartum mothers as an easy and inexpensive alternative that can help mothers in breast milk production.